Robotic Right Lobe Donor Hepatectomy in a G6PD-Deficient Individual: A Case Report on Perioperative Management and Outcomes - R, Ranjith Kumar; V, Hemashree; Sharjun S, Mohamed; M, Abul Yasar; Singh, Pallavi (International Journal of Aquatic Research and Environmental Studies, 2026)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common inherited enzymatic disorder worldwide, affecting approximately 400 million people. Individuals with G6PD deficiency are at risk of acute hemolytic crises when exposed to oxidative stressors, including certain drugs, infections, and surgical stress. The safety of living liver donation in G6PD-deficient individuals has been increasingly recognized, with recent studies demonstrating acceptable perioperative outcomes. However, donor hepatectomy in these patients is associated with a greater drop in postoperative hemoglobin and a marginally increased need for transfusion. We report the case of a 23-year-old male with known G6PD deficiency who underwent successful robotic right lobe donor hepatectomy. The patient was meticulously evaluated preoperatively, and a comprehensive perioperative plan was implemented to minimize oxidative stress and prevent hemolytic complications. Serial monitoring of hemoglobin, reticulocyte count, and urine hemoglobin was performed. The patient had an uneventful intraoperative course and postoperative recovery, with only transient biochemical evidence of hemolysis that resolved without intervention. This case adds to the growing body of evidence supporting the safety of liver donation in G6PD-deficient individuals and highlights the importance of multidisciplinary perioperative management.